Aged Eisenia fetida earthworms exhibit decreased reproductive success. Issue 2 (3rd April 2018) - Penning, K. A.; Wrigley, D. M.
Abstract: The effect of age on male and female reproductive activities was examined in 1–6-year-old age-matched populations of the simultaneous hermaphroditic earthworm, Eisenia fetida, (Annelida; Oligochaeta). As earthworm ages increase from 3 to 6 years, cocoon and hatchling production gradually decreased. Sperm counts from 2-year-old and 5-year-old earthworms did not differ. Old earthworms successfully inseminated young virgin earthworms. Thus, female functions associated with successful cocoon production diminish before the male function. These results indicate that E. fetida earthworms spend up to one-third of their adult life with limited reproductive capabilities.